The Islam in Holly Quran Inferring Study in Tafseer Almezan - Al-Arnawooty, Aiad Mohammed Ali; Fakher Juber, Dhiaa’ (Al-Adab Journal, 2019)
Islam Is to enter the peace and to subject to Allah and the massage of his prophet ( P B U H ) ,legislation , Quran to believe by heart so the work is by religion to maintain the religion . Islam have degrees .the highest is for Abraham (P U H) and the lowest is for ordinary people to keep their blood , money in spite of sins of some of them . The scholar Al-Tabatabee explain the meaning of Islam in that Islam is one for Allah no difference in it and order Allah creatures and explains for them of what Allah introduce of holly books on Allah prophets .It is Islam which is obey the right ,the right of believe and work .it is to subject to the statement issued by God in knowledge and rules that even it was different in quantity and in content in the prophets legislations as in the texts of what Allah says in The Holly Books but it is in reality on order and the difference in legislations in perfection and reduction is without difference and oppositeness and favour among them by degrees .Everybody agrees of it is acceptance and obey for Allah for what Allah wants from the creatures . The scholar Al-Tabatabee concluded in saying that Islam is the religion of Allah and no differences and doubt by the right minds .No questions as you are Muslim .If they question you in the religion you say I Give my believe to Allah and who follow this is religion and no question after religion and ask them : If they became Moslems ,they take the right way accept what Allah reveal on you and on who came before you and they have no questions on you and no conflict between you .If they leave you don not debate them and conflict , the conflict is not in necessary matters .The religion is for Allah and you have to inform .